2019
DOI: 10.3322/caac.21585
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and young adult oncology—past, present, and future

Abstract: There are nearly 70,000 new cancer diagnoses made annually in adolescents and young adults (AYAs) in the United States. Historically, AYA patients with cancer, aged 15 to 39 years, have not shown the same improved survival as older or younger cohorts. This article reviews the contemporary cancer incidence and survival data through 2015 for the AYA patient population based on the National Cancer Institute's Surveillance, Epidemiology, and End Results registry program and the North American Association of Centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
123
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(131 citation statements)
references
References 75 publications
5
123
0
3
Order By: Relevance
“…3 Despite improvements in mortality and survival for patients with pediatric cancers over the past 40 years, progress has been limited for some cancer types diagnosed in childhood, including bone and soft-tissue cancers. 2,[4][5][6][7] Past studies have shown higher mortality with solid tumors versus leukemia and lymphoma and have described disparities in cancer outcomes, such as lower survival for Blacks versus Whites, which warrant further exploration using more recent data. 5,[8][9][10] Thus, this study examined surveillance data for pediatric cancer since 2001 and described recent trends.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Despite improvements in mortality and survival for patients with pediatric cancers over the past 40 years, progress has been limited for some cancer types diagnosed in childhood, including bone and soft-tissue cancers. 2,[4][5][6][7] Past studies have shown higher mortality with solid tumors versus leukemia and lymphoma and have described disparities in cancer outcomes, such as lower survival for Blacks versus Whites, which warrant further exploration using more recent data. 5,[8][9][10] Thus, this study examined surveillance data for pediatric cancer since 2001 and described recent trends.…”
Section: Introductionmentioning
confidence: 99%
“…Because NPCR survival data cover 93% of the US population, it can provide a more comprehensive picture of pediatric cancer survival than past studies using the Surveillance, Epidemiology, and End Results database, that covered ≤28% of the US population at the time of these studies. 5,7 Cancer October 1, 2020…”
Section: Introductionmentioning
confidence: 99%
“…AYA CRCs present with more advanced stage, poorer cell differentiation, and higher prevalence of signet ring cell histology, and the primary tumors are commonly located in the left side of the colon at diagnosis. Although CRC accounted for only 2.5-3.5% of cancer incidence in adolescents from 15 to 19 years old from 2011 to 2015, the 5-year survival rate was lower than in many other cancers (Close et al 2019). Both the incidence and mortality rates of CRC are increasing in China in recent decades (Arnold et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common cancer in incidence and ranks second in terms of cancer-related mortality (Bray et al 2018). Adolescent and young adult (AYA) cancers accounted for 5% of all newly diagnosed invasive cancers in the United States between 2011 and 2015 (Close et al 2019). We have witnessed an overall trend of decreased incidence of CRC over the past few decades as a result of using colonoscopy and other screening modalities in the older population (Connell et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…of osteosarcoma are diagnosed every year [1]. The age distribution of osteosarcoma is bimodal, as the first age peak is recorded between the first and third decades and the second smaller peak (10% of cases) in the sixth decade [1].…”
mentioning
confidence: 99%